Penguatan pendidikan karakter siswa SMP melalui pembelajaran IPA berbasis kearifan lokal - Rina Rahayu; Riva Ismawati; Afni Zulfiani FauziHadi (Rengganis Jurnal Pengabdian Masyarakat, 2026)
Character development is a crucial aspect in preparing students to face the challenges of globalization. Strong character traits are essential for enabling students to adapt and engage positively within their social environment. This community service program aims to strengthen character education among junior high school students through science learning based on local wisdom. The program was carried out at SMPN 9 Magelang using a one-group pretest–posttest design involving 32 seventh-grade students. The activities were conducted over three sessions: (1) administering a pretest and delivering material on the local wisdom of Mount Tidar; (2) deepening the discussion on ecosystems and energy flow in Mount Tidar through group-based activities; and (3) group presentations and administration of the posttest. Integrating scientific concepts with local wisdom was intended to instill character values such as responsibility, environmental awareness, collaboration, and appreciation for local culture. The results show that students participated enthusiastically and actively in discussions and presentations throughout the program. Contextualized science learning that incorporates local wisdom was proven effective in enhancing students’ understanding of ecosystems and energy flow while simultaneously strengthening their positive character traits. Overall, this program demonstrates that local wisdom can serve as an effective medium for educators to internalize character values through science learning at the junior high school level.